2021
DOI: 10.1186/s12967-021-02992-2
|View full text |Cite
|
Sign up to set email alerts
|

Self-supervised deep learning model for COVID-19 lung CT image segmentation highlighting putative causal relationship among age, underlying disease and COVID-19

Abstract: Background Coronavirus disease 2019 (COVID-19) is very contagious. Cases appear faster than the available Polymerase Chain Reaction test kits in many countries. Recently, lung computerized tomography (CT) has been used as an auxiliary COVID-19 testing approach. Automatic analysis of the lung CT images is needed to increase the diagnostic efficiency and release the human participant. Deep learning is successful in automatically solving computer vision problems. Thus, it can be introduced to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(20 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…To facilitate fast COVID-19 diagnosis, Fung, Liu [ 42 ] presented a self-supervised two-stage DL algorithm to segment COVID-19 lesions (Ground-Glass Opacity (GGO) and consolidation) from chest CT images. The suggested DL model incorporated generative adversarial picture in painting, focus loss, and a look ahead optimizer, among other sophisticated computer vision techniques.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…To facilitate fast COVID-19 diagnosis, Fung, Liu [ 42 ] presented a self-supervised two-stage DL algorithm to segment COVID-19 lesions (Ground-Glass Opacity (GGO) and consolidation) from chest CT images. The suggested DL model incorporated generative adversarial picture in painting, focus loss, and a look ahead optimizer, among other sophisticated computer vision techniques.…”
Section: Related Workmentioning
confidence: 99%
“… - Attained average accuracies of 99.4% and 92.9%, respectively, and sensitivity scores of 99.8% and 93.7%. -High complexity -Security is not considered Yes No Python Fung, Liu [ 42 ] Proposing a model incorporating generative adversarial image inpainting, focus loss, and a lookahead optimizer. -High accuracy -High robustness -High energy consumption -High delay -Security is not considered No No Python Radiomic package PyRadiomics Kundu, Basak [ 43 ] Creating a COVID-19 detection system that categorizes CT scan images of the lungs into binary instances.…”
Section: Related Workmentioning
confidence: 99%
“…In [46], it was suggested that a CNN model could be used for COVID-19 lung CT segmentation (SSInfNet). The self-supervised InfNet incorporated various techniques, such as generative adversarial image inpainting, lookahead optimizer, and focal loss.…”
Section: Deep Learning Techniques For Different Image Modalitiesmentioning
confidence: 99%
“…Therefore, their findings indicated that the use and necessity of CT for pediatric patients should be reconsidered, as the model can effectively predict CT outcomes. Fung et al [25] proposed a self-supervised two-stage deep-learning model named SSInfNet to segment COVID-19 lesions (including ground-glass opacity and consolidation) from chest CT images. The authors identified several CT image phenotypes that mediate the potential causal relationship between underlying diseases and age with COVID-19 severity.…”
Section: Comparison Of Medical Images With Clinical Datamentioning
confidence: 99%